Supplement Diets in Relation to Comb Building of Cross Breed Honeybee - Pokhrel, S.; Thapa, R.B. (Journal of the Institute of Agriculture and Animal Science, 2004)
The response of supplement diets was evaluated on comb building of cross-breed honeybee, Apis mellifera Lin. in Chitwan, Nepal during August 2000 to February 2001. The experiment was laid out in a RCB design with five replications, comprising of four feeding treatments: low dose sugar (syrup of 166 g sugar), high dose sugar (syrup of 333 g sugar), modified diet (syrup of 166 g sugar + 30 g pollen substitute) per day, and control. Each hive consisted of five farmed mellifera honeybees and each colony feeding six days with four days interval thus eleven times feedings in total were provided except for the control. Results showed that the colonies fed with modified diet (syrup of 166 g sugar combined with 30 g pollen substitute) was capable to nearly double number of combs/colony (96% increase; 9.8 combs/colony), low dose sugar feeding also increased combs by one-third (36% increase; 6.8 combs/colony) while high dose sugar syrup feeding resulted the lowest number of combs (4% increase; 5.2 combs/colony) mainly due to syrup honey collection rather than comb building. Comb building decreased in control colonies by 4% (4.8 combs/colony) perhaps due to insufficient nutrition during the dearth period. This study provided information that feeding honeybees during off-season is necessary under Chitwan conditions, while modified diet is more suitable for higher comb building of A. mellifera that could facilitate brood production, strengthen colonies, and thus contribute to honey production in flow season. J. Inst. Agric. Anim. Sci. 25:71-74 2004